Analisis faktor-faktor yang mempengaruhi pendapatan pengusaha depot air minum isi ulang di Kecamatan Tungkal Ilir Kabupaten Tanjung Jabung Barat - Surya Asnelly; Siti Hodijah; Candra Mustika (e-Journal Perdagangan Industri dan Moneter, 2019)
This study aims to analyze the socio-economic characteristics of refill drinking water depot entrepreneurs and analyze the influence of opinions of refill drinking water depot entrepreneurs in Tungkal Ilir District, Tanjung Jabung Barat Regency. The data used in this study is primary data obtained through field research sourced from refill drinking water depot entrepreneurs as samples. The sampling method used in this study is Stratified Random Sampling. The analysis tool uses multiple linear regression. Based on the socio-economic characteristics of refill drinking water depot entrepreneurs in Tungkal Ilir District, Tanjung Jabung Barat Regency, some differences can be seen from the majority group of respondents based on the majority gender, age, education level, number of family members, length of business and income of refilled drinking water depot entrepreneurs repeat. The results of data processing the payment of refill drinking water depot entrepreneurs will increase obtained from the regression coefficients of each tube machine variable, education level, and family dependents, which significantly affect the income of refill drinking water depot entrepreneurs. At the same time, the operating hours variable has no significant effect on the payment of refill drinking water depot entrepreneurs in Tungkal Ilir District, Tanjung Jabung Barat Regency. Keywords : Income, Characteristics of refill drinking water depot entrepreneurs.